Let the Sun Shine. - Byrd, Greg (Computer (00189162), 2016)
Clemson University students designed an inexpensive sensor node and cloud computing infrastructure to collect real-time, localized solar irradiation data. This data can be used by consumers and utilities to predict the availability of solar-generated electricity and to manage its use.